ANALISA PENGARUH KEBERADAAN BANGUNAN TERHADAP TINGKAT KEBISINGAN DI SEPANJANG JALAN RAYA PEKANBARU-BANGKINANG - Sandra Septiana; Erwin, '; Defrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The influence of the existence of buildings as a barrier on the noiselevel alongPekanbaru-Bangkinang highway had been studied. A source of noise in this researchwas generated by vechicles passing through along the highway. A tool used to record the noise level was Sound Level Meter (SLM). There were two SLMs used in this measurement, where the first SLM wassituated in the back of the building and thesecond SLM waslocated parallel to the first SLM along the highway without anybuildings.There were four types of buildings used as a noise barrier namely buildingmade of concrete, briks, semi-permanent, and wood. The resultsof the measurementshowed that thehighest noise absorption of about 18.15 %was due to the buildingmade from concrete and followed by bricks, semi-permanent, and woodtheir absorptionvalue of 14.36 %, 13.60 %, and 12.15 % respectively. The highestvalue of absorption ofnoise by concrete building was due to small space volume per percentage of noiseabsorption compared to those of other buildings. The results of this research werecompared to those of Maekawa and ISO9613. The noise absorption in this research wasa little bit lower compared to Maekawa calculation and higher than those for ISO9613with the average error percentage of about 3.35 % and 10.56 % respectively. Themeasurement of noise level as a function of time for one day started from 07.00-18.00showed that the noise level profile had two peaks that was at 12.00-13.00 and 16.00-18.00 with the value respectively of 68.89 dBA and 69.20 dBA. The valueof the noiselevel were also studied as a function of distance and its value declinedverysignificantlyfrom 71.07 dBA to 61.47 dBA when the measurement away from the noisesource.